Social media in the structure of modern network communication - A.G. Astashkin; M.G. Bresler (Ученые записки Казанского университета: Серия Гуманитарные науки)
The functioning of social media in network communications has been studied. The specifics of the linear and network communication models, the behavior of the audience, and the motivation to choose the source of information in each of them have been discussed. The genealogy of the network communication model and the factors that led to its full-scale deployment have been revealed. Social media have been considered as the basis of network communication. Their communication specifics have been compared with the features of mass media serving as a basis of the linear model of communication. The current role of social media in political, sociocultural, and marketing network communications has been analyzed. The paper also touches upon the convergence of mass and social media, as well as upon the evolution of social networks as a form of social media.